Functional Evaluation of Sciatic Nerve Anastomosis Wraped by Freeze Dried Human Amniotic Membrane in Sprague Dawley Rat - Eko Perdana Putra; Pamudji Utomo; Mujaddid Idulhaq (Health and Medical Journal, 2020)
Background. Peripheral nerve injury (PNI) is a common medical condition. The defected nerve, if not repaired as early as possible, can cause long-term denervation and neurotrophy failure for the target organ. This leads to a series of denervation manifestations, such as muscle atrophy, loss of sensory function, etc. and ultimately, these manifestations seriously affect the patient’s sensorimotor function.1,2  Amniotic membranes have been widely used in ophthalmology and skin injury repair because of their anti-inflammatory properties. In this study, we measured therapeutic efficacy and determined if amniotic membranes could be used for sciatic nerve repair.Material and methods. A post test only control group design has been done  in 10 healthy Sprague Dawley rats. In all rats, a unilateral right side sciatic nerve transection was performed and reanastomosed by different methods: Group I (control group): included 5 rats, the anastomosis was done by epineural microsutures using 8/0 nylon. Group II: included 5 rats, the anastomosis was done by epineural microsutures using 8/0 nylon and  then wraped by freeze dried human amniotic membrane. Functional evaluation of nerve recovery was done over 3 weeks postoperatively using walking tract analysis and calculate using Sciatic Functional Index.Result. Functional results showed that there was no significant difference of the sciatic functional index (SFI) between group I and group II.Conclusion. We can conclude that during 3 weeks functional evaluation, there is no significant difference between control group and  experimental group that achieved freeze dried human amniotic membrane.Keywords: sciatic nerve injury, freeze dried human amniotic membrane, walking tract analysis, sciatic functional index.